Highly efficient polariton emission of an ultrastrongly coupled MDMO-PPV OLED. (3rd February 2022) - Chang, Jui-Fen; Ciou, Guo-Sian; Lin, Wei-Hong; Zeng, Gui-Sheng; Chen, Sheng-Hui; Huang, Po-Hsiang
Abstract: We report on a highly efficient polariton emission of poly [2-methoxy-5-(3, 7-dimethyloctyloxy)-1, 4-phenylenevinylene] (MDMO-PPV) organic light-emitting diode (OLED) operating in the ultrastrong coupling regime. MDMO-PPV film with a broadband high absorbance and modest Stokes shift is shown to enable the generation of a large coupling strength and radiative pumping of the lower polariton (LP) mode. Further combining the optimized conditions of cavity design, electron injection, and emission side mirror, we demonstrate that the polariton OLED can produce a spectrally narrow and almost angle-independent emission from the LP mode, with a maximum external quantum efficiency of >0.1% and a Rabi splitting energy of >0.8 eV.